A homogenization method for geometric nonlinear analysis of sandwich structures with initial imperfections. (1st June 2016) - Reinaldo Goncalves, Bruno; Jelovica, Jasmin; Romanoff, Jani
Abstract: A homogenization method for geometric nonlinear analysis of structural core sandwich panels is proposed. The method provides high computational performance based on an efficient separation of scales. In the macroscale, the sandwich panel is discretized with an equivalent single layer of shell elements. The macroscale shell stiffness matrix is nonlinear, obtained from the analysis of a representative volume element. Prescribed displacement boundary conditions are applied to the representative unit based on the strain definitions of the first-order shear deformation theory. Changes in local wavelength in the post-buckling are considered in the analyses. Manufacturing-induced imperfections are introduced to local and global scales. The method allows for description of buckling in these two scales and is shown to hold good accuracy with respect to equivalent 3D FEM models. Examples include web-core and corrugated-core sandwich panels. The method can be extended to any periodic structure of complex local topology. It can be easily implemented to commercial FE packages.